Effect of Gongs Mobilization with Neuromuscular Electrical Stimulation vs Shockwave Therapy Among Patients with Rotator Cuff Tendinopathy - Sarwat Mehmood; Qurrat Ul Ain; Anum Saeed; Ayesha Malik; Areesha Anwar; Sundus Riaz; Syeda Warisha Shakil; Hafiza Mufaz ul Swaba Zanjani (Journal of Health, Wellness and Community Research, 2025)
Background: Rotator cuff tendinopathy is a common cause of shoulder pain and functional limitation, and optimal conservative management remains debated. Gong’s mobilization combined with neuromuscular electrical stimulation (NMES) and extracorporeal shockwave therapy (ESWT) are used clinically, but comparative evidence is limited. Objective: To compare the effectiveness of Gong’s mobilization + NMES versus ESWT in reducing pain and improving disability and shoulder range of motion (ROM) in patients with chronic rotator cuff tendinopathy. Methods: A randomized controlled trial enrolled 60 participants (35–65 years) with ultrasound-confirmed rotator cuff tendinopathy (>3 months). Participants were randomized to Gong’s mobilization + NMES (10 minutes mobilization plus 15 minutes NMES, 35–50 Hz, three sessions weekly) or ESWT (2000 shocks/session at 0.18 mJ/mm², weekly) for eight weeks. Outcomes were assessed at baseline, Week 4, and Week 8 using VAS (primary endpoint: Week 8), SPADI, and goniometric ROM. Results: Both groups improved significantly over time. At Week 8, pain was lower in the Gong’s mobilization + NMES group than ESWT (VAS 2.5 ± 0.8 vs 3.8 ± 1.0; p = 0.002). ROM gains favored Gong’s mobilization + NMES for flexion (152° ± 10 vs 140° ± 12; p = 0.004), abduction (148° ± 11 vs 138° ± 13; p = 0.009), and external rotation (66° ± 7 vs 60° ± 8; p = 0.010), while SPADI improvement was comparable (30.4 ± 6.5 vs 33.8 ± 7.0; p = 0.15). Conclusion: Both interventions were effective, but Gong’s mobilization + NMES produced superior pain reduction and ROM improvement at eight weeks. Keywords: rotator cuff tendinopathy; Gong’s mobilization; neuromuscular electrical stimulation; extracorporeal shockwave therapy; shoulder pain; SPADI; range of motion.
Keywords: Rotator cuff tendinopathy; Gong’s mobilization; neuromuscular electrical stimulation; extracorporeal shockwave therapy; shoulder pain; SPADI; range of motion